Associations of arthritis with functional disability and depressive symptoms in general US adults: NHANES 1988–1994 and 1999–2018 - Xiaoting Liu; Yunzhen Huang; Jinjing Fu; Mayila Mohedaner; Danzengzhuoga; Gan Yang; Zhenqing Yang; Xueqin Li; Xinye Ma; Qiqi Zhang; Zuyun Liu; Xifeng Wu; et al. (Aging Medicine)
Abstract Objectives This study aimed to examine the associations of arthritis with functional disability and depressive symptoms among general US adults. Additionally, it explored the relationship between radiographic knee osteoarthritis (assessed by X‐ray examination) and functional disability. Above findings seek to highlight the need for comprehensive physical and mental health management in individuals with arthritis. Methods We designed a cross‐sectional study utilizing multivariable logistic regression models to examine the associations. Odds ratios (OR) and corresponding 95% confidence intervals (CI) were documented in a crude model and three adjusted models. Participants were from the National Health and Nutrition Examination Survey (NHANES) 1988–1994 and 1999–2018. Arthritis was self‐reported or graded by the Kellgren–Lawrence score after an objective X‐ray examination. Functional disability included disability in activities of daily living (ADL disability), instrumental activities of daily living (IADL disability), and mobility disability. Depressive symptom was assessed using the Patient Health Questionnaire (PHQ). Results We included 22,566 older adults (≥60 years; 10,961 had self‐reported arthritis) for functional disability analysis (2377 older adults with data on X‐ray examination; 1012 had radiographic knee osteoarthritis) and 32,056 adults (≥20 years; 9175 had self‐reported arthritis) for depressive symptom analysis. After controlling for all covariates, self‐reported arthritis was associated with ADL disability (odds ratios [OR]: 2.677; 95% confidence interval [CI]: 2.499–2.868), IADL disability (OR: 2.064; 95% CI: 1.940–2.196), and mobility disability (OR: 2.954; 95% CI: 2.778–3.142), and depressive symptom (OR: 2.177; 95% CI: 1.979–2.395). In participants with data on X‐ray examination, radiographic knee osteoarthritis was only associated with mobility disability (OR: 1.437; 95% CI: 1.183–1.744). Conclusions Self‐reported arthritis was associated with ADL disability, IADL disability and mobility disability, and depressive symptoms. Among participants with X‐ray data, radiographic knee osteoarthritis was only associated with mobility disability in general US adults. Appropriate managements of both physical and mental health are needed for individuals with arthritis.